Conversion hip arthroplasty for failed internal fixation of ipsilateral femoral neck and shaft fractures: a case report - Marlon M. Mencia; Pablo Pedro Hernandez Cruz (Patient Safety in Surgery, 2023)
Abstract Background Ipsilateral femoral neck and hip fractures are uncommon high energy injuries. In the literature no single method of treatment has emerged as superior to the others. A recent publication has documented the successful application of the rendezvous technique using dual-implants for treating these injuries. However in some cases, this technique may fail and revision surgery is required. Case presentation A 67-year old man sustained ipsilateral fractures of his femur and femoral neck in a road traffic accident. His injuries were treated by a dual construct consisting of a retrograde femoral nail and dynamic hip screw. Three months after surgery the hip screw cut out of the femoral head necessitating revision to a total hip arthroplasty. Surgery was carried out using a single stage two part procedure on a standard operating table without having to reposition or redrape the patient. There were no postoperative complications and at 1 year from surgery the patient is satisfied with the result and has returned to work. Conclusion Conversion hip arthroplasty in the presence of dual implants is a technically challenging and unpredictable procedure, with an increased risk of complications. Our surgical approach provides a framework for orthopedic surgeons to safely perform this complex procedure.